Diffusion of energy technology innovations in Portugal and perspectives for decarbonization - Bento, N.; Fontes, M. (P2M 1st Webinar on CO2 capture and utilization: insights from academia and industry, 2020)
We present the results of the comparative analysis of the diffusion of energy technologies in Portugal in relation to the pioneer countries. It includes recent developments and reflection on the determinants of observed trends, in order to draw lessons to formulate perspectives for the decarbonization of systems with the characteristics of the national economy.